Selective and generic photocatalytic oxidation of alcohol with Pd-TiO2 thin films: butanols to butanal/butanone with different morphologies of Pd and 0.5 theta(Pt)-Pd counterparts - Salgaonkar, Kranti N.; Kale, Sandip R.; Nalajala, Naresh; Mansuri, Sayana; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2023)
The present study reports on the photocatalytic oxidation of butanols to butanal/butanone using thin film form of facet-dependent nano-Pd supported on commercial TiO2 under one-sun condition and demonstrates the generic nature. Pd-nanocube (Pd-NC(100)), Pd-truncated octahedron (Pd-TO (100) and (111)), polycrystalline (Pd-PC), and their counterparts with half-a-monolayer Pt-coated on Pd (0.5 theta(Pt)-Pd)) have been used as co-catalyst. A potentially scalable thin film form of Pd/TiO2 photocatalyst, prepared by drop-casting method, has been employed to study oxidation of n-butanol, 2-butanol, and iso-butanol to corresponding aldehyde/ketone. 100% selectivity is demonstrated to respective aldehyde/ketone with any catalyst used in the present study with varying degree of butanols conversion by NMR. 0.5 theta(Pt)-Pd-TO/TiO2 shows the highest conversion of 2-butanol to butanone (13.6% in 4 h). Continuous 10 h of reaction with the most active 0.5 theta(Pt)-Pd-TO/P25 catalyst demonstrates 31% conversion of 2-butanol to butanone, and catalyst recyclability has been demonstrated. The present protocol can be scalable to large scales to maximize the conversion in direct sunlight. Due to its generic nature, the current method can also be applied to many other alcohols and substrate molecules.
Keywords: energy conversion; Nanomaterials; Oxidation; Photocatalysis; Sustainability

Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania